Designing and conducting survey research : a comprehensive guide - Rea, Louis M.; Parker (San Francisco, CA :: Jossey-Bass, a Wiley brand, 2014)
"This book is a comprehensive, practical guide to conducting survey research. The book covers all major components of the method, including construction of the instrument, administration of the process, and analysis and reporting of results. The authors de-mystify statistics and enable readers to conduct a sample survey research project from initial conception of the research focus to the preparation of the final report, including basic statistical analysis of the data"--
Includes bibliographical references (pages 321-323) and index.
Keywords: POLITICAL SCIENCE / Public Affairs & Administration; SOCIAL SCIENCE / Research; Sampling (Statistics); Social surveys; Social sciences -- Statistical methods